Synthesis, characterization and biological activity of two Schiff base ligands and their nickel(II), copper(II), zinc(II) and cadmium(II) complexes derived from S-4-picolyldithiocarbazate and X-ray crystal structure of cadmium(II) complex derived from pyridine-2-carboxaldehyde - Khoo, Teng Jin; Break, Mohammed Khaled; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim; Ali, A. M.; Cowley, Andrew R.; Watkin, D. J.; Tarafder, M. T. H. (Elsevier, 2014)
A substituted dithiocarbazate moiety has been prepared using 4-picolylchloride hydrochloride to obtain S-4-picolyldithiocarbazate (S4PDTC) and its by-product (S4diPDTC). Two Schiff bases were synthesized by reacting S-4-picolyldithiocarbazate with pyridine-2-carboxaldehyde (Pc4PDTC) and 4-carboxybenzaldehyde (Cb4PDTC). Ni(II), Cu(II), Zn(II) and Cd(II) complexes of the Schiff bases were characterized by various physico-chemical and spectroscopic methods viz. CHNS elemental analyses, molar conductivity, IR, UV–Vis, 1H and 13C NMR, mass spectrometry and magnetic susceptibility. X-ray crystallographic analysis has been carried out on the by-product and the Cd complex of the ligand derived from (Pc4PDTC). The ligands and their metal complexes were assayed in vitro for cytotoxic, antimicrobial and antioxidant activities. The Pc4PDTC Schiff base showed moderate cytotoxicity against human promyolicytic leukemic (HL60) cell line with a CD50 value of 9 μg/cm3 while Cb4PDTC was inactive. Complexing Pc4PDTC with cadmium(II) and copper(II) enhanced its cytotoxicity against the human promyolicytic leukemic cell line (HL60) from moderately to highly active. S4PDTC showed marked antimicrobial activity against bacteria but was inactive towards fungi. Copper(II) and cadmium(II) complexes of the two Schiff bases showed clear inhibition zones for most of the fungi and bacteria tested. Antioxidant properties of Pc4PDTC and Cb4PDTC Schiff bases were comparable to the commercially available buthylatedhydroxytoluene (BHT).